Pengaruh Parkir Pada Badan Jalan Terhadap Kinerja Ruas Jalan Sutomo Kota Medan - Sindi Gustari; Marwan Lubis; M. Husni Malik (aspal, 2023)
The city of Medan has experienced very rapid development from year to year, this has resulted in the increasingly dense traffic flow in the city. And one of the roads that experience congestion due to parking on the road body and affect the performance of road sections and is also the location of research, namely on Jalan Sutomo. Data collection techniques include survey data of traffic volume, parking volume, road section capacity and V/C ratio value. The data obtained were analyzed using the 1997 Indonesian Road Capacity Manual regulations. The traffic volume with side obstacles (H) was 504 events / hour, the road capacity before there was on street parking 6665.5 smp/hour and the road capacity after there was on street parking 4795.1 smp/hour. There is a fairly high increase due to vehicle parking activities on the road body in a very. The highest traffic density on Fridays occurs in the time interval 12.00 - 13.00. The level of road service before there is on street parking is up to level C, where the value of the V/C Ratio reaches 0.60. As for the level of road servants after on-street parking is up to level D, where the V/C Ratio value reaches 0.84, with an average speed of 44.1 km/h. With these conditions, if not handled immediately, it will affect traffic performance.